Variation in the circumsporozoite protein of Plasmodium falciparum: vaccine development implications. - Kavita Gandhi; Mahamadou A Thera; Drissa Coulibaly; Karim Traoré; Ando B Guindo; Amed Ouattara; Shannon Takala-Harrison; Andrea A Berry; Ogobara K Doumbo; Christopher V Plowe (PLoS ONE)
The malaria vaccine candidate RTS,S/AS01 is based on immunogenic regions of Plasmodium falciparum circumsporozoite protein (CSP) from the 3D7 reference strain and has shown modest efficacy against clinical disease in African children. It remains unclear what aspect(s) of the immune response elicited by this vaccine are protective. The goals of this study were to measure diversity in immunogenic regions of CSP, and to identify associations between polymorphism in CSP and the risk of P. falciparum infection and clinical disease. The present study includes data and samples from a prospective cohort study designed to measure incidence of malaria infection and disease in children in Bandiagara, Mali. A total of 769 parasite-positive blood samples corresponding to both acute clinical malaria episodes and asymptomatic infections experienced by 100 children were included in the study. Non-synonymous SNP data were generated by 454 sequencing for the T-cell epitopes, and repeat length data were generated for the B-cell epitopes of the cs gene. Cox proportional hazards models were used to determine the effect of sequence variation in consecutive infections occurring within individuals on the time to new infection and new clinical malaria episode. Diversity in the T-cell epitope-encoding regions Th2R and Th3R remained stable throughout seasons, between age groups and between clinical and asymptomatic infections with the exception of a higher proportion of 3D7 haplotypes found in the oldest age group. No associations between sequence variation and hazard of infection or clinical malaria were detected. The lack of association between sequence variation and hazard of infection or clinical malaria suggests that naturally acquired immunity to CSP may not be allele-specific.